Changes in European wind energy generation potential within a 1.5 °C warmer world. (17th May 2018) - Hosking, J Scott; MacLeod, D; Phillips, T; Holmes, C R; Watson, P; Shuckburgh, E F; Mitchell, D
Abstract: Global climate model simulations from the ' Half a degree Additional warming, Prognosis and Projected Impacts' (HAPPI) project were used to assess how wind power generation over Europe would change in a future world where global temperatures reach 1.5 °C above pre-industrial levels. Comparing recent historical (2006–2015) and future 1.5 °C forcing experiments highlights that the climate models demonstrate a northward shift in the Atlantic jet, leading to a significant ( p  < 0.01) increase in surface winds over the UK and Northern Europe and a significant ( p  < 0.05) reduction over Southern Europe. We use a wind turbine power model to transform daily near-surface (10 m) wind speeds into daily wind power output, accounting for sub-daily variability, the height of the turbine, and power losses due to transmission and distribution of electricity. To reduce regional model biases we use bias-corrected 10 m wind speeds. We see an increase in power generation potential over much of Europe, with the greatest increase in load factor over the UK of around four percentage points. Increases in variability are seen over much of central and northern Europe with the largest seasonal change in summer. Focusing on the UK, we find that wind energy production during spring and autumn under 1.5 °C forcing would become as productive as it is currently during the peak winter season. Similarly, summer winds would increase driving up wind generation to resemble levels currently seen in spring and autumn. We conclude that the potential for wind energy in Northern Europe may be greater than has been previously assumed, with likely increases even in a 1.5 °C warmer world. While there is the potential for Southern Europe to see a reduction in their wind resource, these decreases are likely to be negligible.